Aesculetin Inhibits Proliferation and Induces Mitochondrial Apoptosis in Bladder Cancer Cells by Suppressing the MEK/ERK Signaling Pathway - Han, Li; Li, Peiwu; Fu, Xu; Huang, Zhenzhen; Yin, Wen (Anti-cancer agents in medicinal chemistry, 2023)
Aesculetin (AE), a natural coumarin derivative found in traditional medicinal herbs, has a variety of pharmacological effects. However, the role of AE and its molecular mechanisms of action on bladder cancer remains undefined. The study aims to explore the anti-tumor effects of AE on bladder cancer cells and the associated molecular mechanisms. We performed a Cell Counting Kit-8 assay to examine the inhibitory effects of AE on 5637 and T24 cells. The anti-tumor effects of AE on 5637 cells were evaluated by performing colony formation, living/dead cell staining, apoptosis, cell cycle, migration and invasion assays. The expression levels of related proteins were determined using western blotting. The viability of 5637 and T24 cells was decreased by AE. AE significantly inhibited colony formation, arrested the cell cycle at the G0/G1 phase, decreased migration and invasion, decreased the mitochondrial membrane potential and increased apoptosis in 5637 cells. Western blotting results showed the release of cytochrome C from mitochondria; the activation of caspase-9 and caspase-3; decrease in CDK4, CCND1, MMP2 and MMP9 levels and an increase in the BAX/BCL-2 protein ratio after treatment with AE. AE also downregulated the levels of p-ERK and p- MEK proteins. Pre-treatment with U0126 significantly enhanced the anti-tumor effects of AE. AE inhibited the proliferation and induced the apoptosis of bladder cancer cells through the MEK/ERK pathway. These findings provide possible therapeutic strategies for bladder cancer.